Clinical Overview of MDM2/X-Targeted Therapies - Burgess, Andrew; Chia, Kee Ming; Haupt, Sue; Thomas, David; Haupt, Ygal; Lim, Elgene (Frontiers in Oncology, 2016)
MDM2 and MDMX are the primary negative regulators of p53, which under normal conditions, maintain low intracellular levels of p53 by targeting it to the proteasome for rapid degradation, and inhibiting its transcriptional activity. Both MDM2 and MDMX function as powerful oncogenes and are commonly over-expressed in some cancers, including sarcoma ( 20%), and breast cancer ( 15%). In contrast to tumours that are p53 mutant, whereby the current therapeutic strategy is restore the normal active conformation of p53, MDM2 and MDMX represent logical therapeutic targets in cancer for increasing wild type (WT) p53 expression and activities. Recent preclinical studies suggest that there may also be situations that MDM2/X inhibitors could be used in p53 mutant tumours. Since the discovery of nutlin-3a, the first in a class of small molecule MDM2 inhibitors that binds to the hydrophobic cleft in the N-terminus of MDM2, preventing its association with p53, there is now an extensive list of related compounds. In addition, a new class of stapled-peptides that can target both MDM2 and MDMX have also been developed. Importantly, preclinical modeling, which have demonstrated effective in vitro and in vivo killing of WT p53 cancer cells, have now been translated into early clinical trials allowing better assessment of their biological effects and toxicities in patients. In this overview, we will review the current MDM2 and MDMX targeted therapies in development, focusing particularly on compounds that have entered into early phase clinical trials. We will highlight the challenges pertaining to predictive biomarkers for and toxicities associated with these compounds, as well as identify potential combinatorial strategies to enhance its anti-cancer efficacy